Pemikiran KH. Imam Zarkasyi (1910–1985) Tentang Pendidikan DanRelevansinya Dengan Dunia Pendidikan Islam Kontemporer - Ru’uliyanah Sabrianti (4, 2026)
Abstract This study comprehensively examines the educational thinking of KH. Imam Zarkasyi, a central figure and founder of the Darussalam Gontor Modern Islamic Boarding School, and the relevance of his ideas in addressing the challenges of contemporary Islamic education. This study uses a qualitative approach through literature review, examining the works, speeches, and educational practices developed by KH. Imam Zarkasyi. The main focus of the discussion is directed at the concept of integral Islamic education, which emphasizes not only cognitive aspects but also harmonizes moral, intellectual, and spiritual dimensions in a balanced manner. One of KH. Imam Zarkasyi's important contributions is the formulation of the Panca Jiwa values: sincerity, simplicity, independence, Islamic brotherhood, and freedom. These values ​​are not limited to the normative level but are systematically internalized in Islamic boarding school life to shape the character of students who are independent, have integrity, and are socially conscious. Furthermore, Zarkasyi's thinking firmly rejects the dichotomy between religious knowledge and general knowledge. He viewed all knowledge as a unified whole, rooted in divine values ​​and directed toward the welfare of the people. From KH. Imam Zarkasyi's perspective, the role of educators is also crucial, as educators who not only transmit knowledge but also serve as moral and spiritual role models for students. Institutionally, he emphasized the importance of Islamic boarding schools' independence through the management of productive waqf (endowments). In the current context of globalization and digital development, KH. Imam Zarkasyi's educational thinking remains relevant as a foundation for the development of modern Islamic education, adapting to changing times, yet firmly rooted in divine values. Abstrak Penelitian ini membahas secara komprehensif pemikiran pendidikan KH. Imam Zarkasyi, tokoh sentral dan pendiri Pondok Modern Darussalam Gontor, serta relevansi gagasan-gagasannya dalam menjawab tantangan pendidikan Islam kontemporer. Kajian ini menggunakan pendekatan kualitatif melalui studi kepustakaan dengan menelaah karya-karya, pidato, dan praktik pendidikan yang dikembangkan oleh KH. Imam Zarkasyi. Fokus utama pembahasan diarahkan pada konsep pendidikan Islam integral yang tidak hanya menekankan aspek kognitif, tetapi juga mengharmoniskan dimensi akhlak, intelektual, dan spiritual secara seimbang. Salah satu kontribusi penting KH. Imam Zarkasyi adalah perumusan nilai-nilai Panca Jiwa, yakni keikhlasan, kesederhanaan, kemandirian, ukhuwah Islamiyah, dan kebebasan. Nilai-nilai ini tidak berhenti pada tataran normatif, tetapi diinternalisasikan secara sistematis dalam kehidupan pesantren untuk membentuk karakter santri yang mandiri, berintegritas, dan memiliki kepedulian sosial. Selain itu, pemikiran Zarkasyi secara tegas menolak dikotomi antara ilmu agama dan ilmu umum. Ia memandang seluruh ilmu sebagai satu kesatuan yang bersumber dari nilai ketuhanan dan harus diarahkan untuk kemaslahatan umat. Peran pendidik dalam perspektif KH. Imam Zarkasyi juga sangat sentral, yakni sebagai murabbi yang tidak hanya mentransfer ilmu, tetapi menjadi teladan moral dan spiritual bagi peserta didik. Di sisi kelembagaan, ia menekankan pentingnya kemandirian pesantren melalui pengelolaan wakaf produktif. Dalam konteks globalisasi dan perkembangan digital saat ini, pemikiran pendidikan KH. Imam Zarkasyi tetap relevan sebagai fondasi bagi pengembangan pendidikan Islam yang modern, adaptif terhadap perubahan zaman, namun tetap berakar kuat pada nilai-nilai ilahiyah